Exploring family disaster communication before, during and after disaster in Brgy. Baging Sillangan - Diaz, Nicole Marie E.; Gabriel, Florenda S. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
This qualitative study explored the communication patterns of families before, during, and after disaster of Brgy. Bagong Silangan residents. It illustrated the communication process of households by describing the topics being discussed, sources of information, manner of sharing information, and how they make use of the information received. Data were gathered by face-to-face interviews of 19 households. Phenomenological approach was used to describe the communication patterns and identify communication themes. Security of life and security of property were the common themes that emerged during the three disaster phases. Results reveal four types of family communication involving husband and wife or parents and children - instruction, storytelling, command, and discussion. Communication pattern change from protective to consensual depending on the age of children involved and the stage in the disaster phase.
Thesis classification : F
Thesis (B.S. Home Economics)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Families -- Philippines; Communication in families -- Philippines